Fluid Flow-inspired Curvature-aware Print-paths from Hexahedral Meshes for Additive Manufacturing. (June 2023) - Cam, Serhat; Gunpinar, Erkan
Abstract: Thanks to recent improvements, computational methods are able to produce high-quality hexahedral meshes, whose hexahedrons are arranged along the principal curvature directions of the input surfaces. Curvature-aware print-paths following these curvature directions have been recently proposed by Gunpinar and enable reduction in stair-stepping effect in the printed parts. However, crosswise contacts can exist between the print-paths (i.e., print-paths are quasi-perpendicular to each other), which is undesirable as failures may occur particularly at those contact regions. Therefore, the present work aims at generation of curvature-aware print-paths without crosswise contacts between them. To solve this problem, we inspire from fluid flow and imitate (laminar) streamlines for an inlet and an outlet of a duct for designing print-paths. A hexahedral mesh is decomposed into blocks (cuboid-like sub-volumes), each of which is covered with fluid flow-inspired print-paths. A multi-axis (collision-free) additive manufacturing (AM) planning technique is also proposed. As a proof of concept, fluid flow-inspired curvature-aware print-paths are validated using a multi-axis AM simulator and machine. Graphical abstract: Highlights: A fluid-flow inspired print-path planning technique from hexahedral meshes. Continuous print-paths and preventing problems of cross-wise contacts. Curvature-aware print-paths to cover features of a part in a conformal manner. Support of multi-axis additive manufacturing. Adjustment of print-path orientations according to specific guidelines.